Kontribusi Kompetensi Guru terhadap Kemampuan Literasi Siswa Kelas VI Madrasah Ibtidaiyah di Kabupaten Boyolali - Siti Badriyah; Atin Chusniyah (Lembaga Yasin AlSys, 2026)
The low level of literacy among sixth-grade students of Madrasah Ibtidaiyah during the transition to secondary education has become a crucial issue that demands the optimization of teachers’ pedagogical and professional competencies. This study aims to analyze the effect of teacher competence on the literacy level of sixth-grade Madrasah Ibtidaiyah students in Boyolali Regency through a quantitative explanatory approach. This study involved 150 students as the sample selected using simple random sampling. Data were collected through a validated teacher competence questionnaire and an AKM-standard reading literacy test, and were then analyzed using simple linear regression. The results showed that teacher competence had a positive and significant effect on students’ literacy ability (p < 0.05). The coefficient of determination test showed that teacher competence contributed 50.1% to explaining the variation in students’ literacy ability, while the remaining proportion was influenced by other factors outside the research model. These findings affirm that teacher competence is not merely a supporting variable, but an important determinant in building critical literacy in elementary schools. Thus, this study emphasizes the importance of strengthening sustainable literacy-based teacher professional development programs in order to improve the quality of Madrasah Ibtidaiyah graduates.